Morphometric and Histological Observations on the Testis of Mule and Donkey of Himalayan Region - Pathak, Virender; Sheikh, Andleeb; Rajput, Rajesh; Bhardwaj, R. L.; Sharma, Arvind (Indian Journal of Veterinary Anatomy, 2013)
Generally in mules the spermatogenesis does not advance beyond spermatocytes. In the present study, comparative and morphometric evaluation was done on the testis of mule and donkey of Himalayan region. It was observed that the mules had seminiferous tubules of smaller diameter with the mean value of 237.95±6.27 µ. The germ cells in mule’s testis showed that spermatogonia did not mature beyond spermatocyte stage, therefore no mature spermatozoa were found on the apical surface of Sertoli cells and in the lumen of seminiferous tubules. The mean number (8.30±0.82) of Leydig cells in mules was significantly lower (16.0±0.88) than that of donkeys. The nuclear diameter and cellular diameter of Leydig cells were significantly higher in donkey than the mule. However, the mean Sertoli cells per seminiferous tubules in the tesits of mule and donkey didn’t differ significantly. The data in the present study suggested that the lower number of Leydig cells could be the reason, that seminiferous tubule could not sustain complete spermatogenesis in mule.